PEMBELAJARAN MODEL VIRTUAL CLASS PADA MATERI YOGA ASANAS DI SMA NEGERI 3 PALU: I Made Nuhari Anta, I Kayan Setiawan - I Made Nuhari Anta; I Kayan Setiawan (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2021)
The Covid-19 pandemic has had a major impact on the world of education, so it has to adapt to doing virtual class (online) learning. Like learning yoga asanas at SMA Negeri 3 Palu, which must apply virtual class learning models with practical materials, they will find serious problems. The formulation of the problem is: 1. How is the virtual class model learning on yoga asanas at SMA Negeri 3 Palu? 2. How is the learning process through a virtual class model in learning yoga asanas at SMA Negeri 3 Palu? The method in this study is a qualitative descriptive method as an assessment of the problem in this study. The results are 1. In learning the virtual class model, the teacher uses online applications such as google meet, whatsapp group, and quizizz and is balanced with the provision of yoga asanas tutorial videos. 2. The learning process of the virtual class model consists of several stages, namely the planning or preparation stage and the implementation stage. The planning stage consists of the process of making lesson plans, Flyer invitations to enter learning, teaching materials or materials in the form of power points, and quizzz as the evaluation stage.